2012
DOI: 10.1007/s11746-012-2014-1
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization Behavior of Diacylglycerol‐Rich Oils Produced from Rapeseed Oil

Abstract: We examined the crystallization behavior of high-melting fractions in liquid oil containing high concentrations of diacylglycerols (DAG [80%) (hereafter referred to as DAG-rich oil). By differential scanning calorimetry and optical microscopy at moderate cooling rates, crystallization in the DAG-rich oil was detected at around 6°C. It was found that the crystallization extent increased with decreasing temperatures of crystallization below 0°C. A gas chromatographic analysis was performed on the crystallized fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 44 publications
2
30
0
Order By: Relevance
“…Peaks for StO, StSt, and PP DAGs have been confirmed by comparison with pure standards. Other peaks are tentatively assigned by comparison with Saitou et al .…”
Section: Resultsmentioning
confidence: 84%
“…Peaks for StO, StSt, and PP DAGs have been confirmed by comparison with pure standards. Other peaks are tentatively assigned by comparison with Saitou et al .…”
Section: Resultsmentioning
confidence: 84%
“…The granular crystals might be β form, while the round-shaped crystals might be β polymorph since β form had a larger crystal than β form. Saitou et al had also found that small round-shaped crystals with diameters ranging 5-20 μm observed in DAG-enriched oil at about 6 29 .…”
Section: Crystallization and Melting Propertiesmentioning
confidence: 91%
“…4a, Table 2 . This broad peak peak I might be caused by the different crystallization rates of different DAG components 29 . And peak II was about 5 times larger than peak I, which meant the second crystallization stage formed more crystal fraction than the first one did.…”
Section: Acylglycerols and Fatty Acid Composition Of Desomentioning
confidence: 99%
“…As for DAGs with the same molecular conformation, the melting point increases with increasing fatty acid saturation, as observed in DSC results (heating rate: 1 • C/min) of purified 1,3-dioleoyl-sn-glycerol (26.33 • C), 1-palmitoyl-3-oleoylsn-glycerol (43.63 • C), and 1,3-dipalmitoyl-sn-glycerol (69.70 • C; Xu & Cao, 2017a). In the work of Saitou et al (2012), for example, when DAG-rich oils (DAG: 85.0%) produced from rapeseed oils were cooled at 3 • C, the resultant crystals were mainly composed of 1,3-DAGs instead of 1,2-DAGs. In addition, the DAG fractions have been found to crystallize in a sequential manner with high-melting molecules such as 1,3-disaturated DAGs crystallizing first followed by 1,3-saturated-unsaturated and 1,3-diunsaturated DAGs (Saitou et al, 2012).…”
Section: Crystallization and Melting Behaviormentioning
confidence: 58%
“…In the work of Saitou et al. (), for example, when DAG‐rich oils (DAG: 85.0%) produced from rapeseed oils were cooled at 3 °C, the resultant crystals were mainly composed of 1,3‐DAGs instead of 1,2‐DAGs. In addition, the DAG fractions have been found to crystallize in a sequential manner with high‐melting molecules such as 1,3‐disaturated DAGs crystallizing first followed by 1,3‐saturated‐unsaturated and 1,3‐diunsaturated DAGs (Saitou et al., ).…”
Section: Physicochemical Properties Of Slsmentioning
confidence: 99%